Why Marx still matters. (1st January 2013) - Wisman, Jon D.
This article explores why a deep understanding of Marx's project is essential for developing an adequate science of society. Marx focused on two aspects of social reality that are critical to its understanding, but are absent from the contemporary practice of social science. First, he viewed humanity's struggle to overcome nature's scarcity as causally and dynamically related to social organisation and social consciousness. Second, he unfolded a theory of our self-creation, the manner in which products of our manual and intellectual labour act back upon us to create us socially and intellectually. To the extent that we lose consciousness of this authorship, our freedom is constrained. We are controlled by our own creations. Our freedom requires a social science with Marx's breadth to enable us to recover awareness of our authorship of our social creations and thereby be empowered to control them, as opposed to being their victims.